Analisis Pengelolaan Keuangan Badan Usaha Milik Desa (BUMDES) dalam Meningkatkan Pendapatan Desa (Studi Kasus di Desa Muara Sungai, Kecamatan Cambai, Kota Prabumulih) - Rika Fitri Ramayani; Yulita Eka Fitri (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine financial management in increasing village income at BUMDes Hope to Move Forward Together Muara Sungai Village, Cambai District, Prabumulih City—types of research Quantitative Descriptive. The data used is primary and secondary. Technique data collection, namely, observation, interviews, and documentation. Analysis Techniques Researchers must obtain accurate data so that it is easy to analyze further data. The research results show that BUMDes Management’s hope of moving forward includes several stages: the source of capital from the Village Revenue and Expenditure Budget (APBD) for Fiscal Years 2020, 2021, and 2022. Financial management of BUMDes and the businesses they run completely increase the income of the village community due to the lack of understanding from village communities regarding BUMDes financial management, and the income of the business being carried out needs to be fully in line with that expected. Allocation of accountability reports in recording expenses and revenue of BUMDes Hope to move using profit and loss statement notes and cash book but still need to start using balance sheet notes. Financial management in BUMDes Hope to move forward has yet to meet its income public fully.